Amplifying Flood Risk Across the Lower Yellow River Basin, China, Under Shared Socioeconomic Pathways - Song, Jinbo; Zhang, Qiang; Wu, Wenhuan; Singh, Vijay P.; Shen, Zexi; Wang, Gang; Xu, Chong-Yu (Frontiers in Earth Science, 2022)
The ecological conservation and high-quality development of the Yellow River Basin (YRB) has been adopted as a major national strategy of China. However, the YRB is still afflicted by floods. Here we propose a flood risk indicator using direct economic loss degree, and improve the SNRD (station-based non-linear regression downscaling model) and simulate extreme precipitation processes. The correlation coefficient of downscaled average extreme precipitation of CMORPH and CMIP6 data reached 0.817. Moreover, we evaluated flood risk and flood hazard across the YRB based on the 6th phase Coupled Model Intercomparison Project (CMIP6) under different SSPs. Under the SSP126, SSP245, and SSP585 scenarios, the areas with increasing flood hazards during 2015 to 2045 accounted for 65.2%, 69.0%, 64.5% of the entire YRB. In the spatial pattern, flood hazards decreased from southeastern to northwestern parts of the YRB. When compared with the spatial pattern of flood risks in 2015, regions with high flood risks expanded slightly and regions with low flood risks shrunk slightly. Higher flood risks can be observed in the middle and lower YRB and particularly in the lower YRB. These findings are critical for mitigation of flood risk across the YRB under warming climate.